Analyzing the effect of the elastane-containing dual-core weft yarn density on the denim fabric performance properties. Issue 1 (2nd January 2016) - Ertaş, Osman Gökhan; Zervent Ünal, Belkıs; Çelik, Nihat
Abstract : Denim fabrics form today's mostly utilized fabric type. As is the case with the other textile products, there are many factors affecting the properties and the performance of the denim products. Within the scope of this study, we have evaluated the effect of the density changes in the use of the dual-core threads – used in an ever-increasing fashion in the textile industry – in weft have on the fabric properties. We have analyzed the extent to which the weight, size, elasticity, tensile strength, and cost properties of the denim fabrics woven with the dual-core weft thread in various densities are affected by the changes in the number of dual-core weft threads per unit length. In conclusion, we have come to such striking remarks as that the construction has a much more impact on the fabric width and thus on the unit weight than the elasticity ratio, and that density changes in the elastane-containing threads cause serious differences on the fabric's color values.